Protocol for induction of estrus in anestrus wool sheep and their productive performance - Verdoljak, Juan José (2017)
The aim of the study was to evaluate the effect of the climate and a heat synchronization protocol on the onset of puberty, gestation and lambing of Texel x Romney ewes bred outside the breeding season. The experiment was carried out at the INTA Experimental Station (EEA) (Corrientes, Argentina) with 26 Texel x Romney ewes of 11 months of age and 47.0 ± 2.2 kg of body weight. A protocol of estrus synchronization using intravaginal sponges with medroxyprogesterone acetate - MAP (60 mg) for seven days and 400 IU of eCG at the removal of the sponges was applied. Two fertile Dorper males were introduced on the day of sponge removal and the diagnosis of pregnancy by rectal ultrasonography was performed 50 days after the mating. Meteorological data were obtained to calculate the temperature-humidity index (ITH) and to determine the degree of caloric stress. Results showed that 69.2% of the sheep were mated at 48 h, 15 ewe-lambs were considered as pregnant and nine of them lambed. During gestation, the sheep were exposed to severe and extreme stress on 23 and 50% of the days. The mean birth weight was 1.5 ± 0.5 kg.